Prescient diagnostic analysis for boron nutritional status in soy crops - Traspadini, Edilaine Istéfani Franklin [UNESP]; Wadt, Paulo Guilherme Salvador; de Mello Prado, Renato [UNESP]; Roque, Cassiano Garcia; Wassolowski, Carlos Roberto (Springer Nature, 2023)
Boron is the most limiting micronutrient for soybean yield; therefore, accurate identification of its nutritional status is important for adequate fertilization management and maximize soybean yield potential. Currently, tools for nutritional status interpretation of B, such as the CND and DRIS are used; however, their efficacy is not considered to identify the true nutritional status of B. In this research, we investigated the efficacy of these methods to identify the nutritional status of B in 140 commercial soybean crops to obtain nutritional standards for the DRIS and CND methods. In addition, an experiment of B dose calibration (0, 300, 600, 1200 and 1800 g ha−1) was installed to assess the quality of nutritional diagnoses using the PDA. The experimental approach tested the limits of 0.25, 0.50, and 1.00 for the NRr and values of 1%, 5%, or 10% for YR. The DRIS method was more effective, and, on average, its variations increased yield by 27% compared to CND, with the best performance of DRIS when NRr = 1.00 was adopted with 10% for YR. This study highlights the need for reliable and accurate diagnostic methods with global implications for crop sustainability by improving the efficacy of B fertilization programs and crop yield.